Taking a Stand through Digital Games - An empirical procedure among consciousness, learning and participation - Enrico Gandolfi (Academicus, 2018)
The article focuses on an empirical procedure aimed to harness digital games in exploring sensible issues in social research. By merging qualitative and creative methods and taking into account suggestions from Sociology, Media Studies, and Game Studies, the suggested approach combines single interviews, focus groups and participative design exercises according to a creative learning path. In order to put its effectiveness to the test, four groups of players (N: 20) with different attitudes toward play were recruited for addressing the theme of sustainability. The digital games Crusader Kings 2 and Sid Meier’s Alpha Centauri were selected as facilitating tools due to the related pertinence. Results show an increment of consciousness and awareness about the topic and a noteworthy potential in engaging subjects and stimulating their feedback in empirical investigations. In turn, some limits emerged to the extent that further interventions are required to stress and relativize the proposal.